A meal with mixed soy/whey proteins is as efficient as a whey meal in counteracting the age-related muscle anabolic resistance only if the protein content and leucine levels are increased. Issue 12 (26th November 2018) - Jarzaguet, Marianne; Polakof, Sergio; David, Jérémie; Migné, Carole; Joubrel, Gwénaële; Efstathiou, Théo; Rémond, Didier; Mosoni, Laurent; Dardevet, Dominique
Abstract : With aging, skeletal muscle becomes resistant to the anabolic effect of dietary proteins and sarcopenia develops. Abstract : With aging, skeletal muscle becomes resistant to the anabolic effect of dietary proteins and sarcopenia develops. Animal proteins, which are rich in leucine, are recommended for the elderly, but it is not known whether their replacement by plant proteins would maintain the health and physical independence of this population. Aged rats were fed with animal proteins (casein and whey proteins) with different leucine contents and compared to rats fed with diets in which whey was substituted with soy proteins and by increasing the total protein content or not. Our results clearly showed that the meal with mixed soy/whey proteins allowed the anabolic response of skeletal muscle during aging only if the protein content was increased by 25%. Indeed, if the protein content of the soy/whey diet was decreased to a similar protein content such as a whey diet, i.e. 13%, the anabolic effect decreased. The same observation was recorded if the whey proteins were totally substituted with soy proteins.